Effect of metal fluorides on chromium ions doped bismuth borate glasses for optical applications. (March 2019) - Haritha, L; Chandra Sekhar, K; Nagaraju, R; Ramadevudu, G; Sathe, Vasanth G; Shareefuddin, Md.
Abstract : Fluoride based glasses with composition CaF2 –ZnF2 –Bi2 O3 –B2 O3 doped with chromium ions have been investigated using physical, optical, electron paramagnetic resonance (EPR), Fourier-transform infrared spectroscopy (FTIR), and Raman studies. The amorphous nature of samples was confirmed from x-ray diffraction spectra. The density is evaluated from the Archimedes principle and the values of optical band gap and Urbach energy values were evaluated from the optical absorption spectra. Thus, molar volume, refractive index, etc., were also evaluated. The observed decrease in density and the optical band gap with CaF2 is explained using the crystalline density of metal fluorides and the ionicity of fluorine ions, respectively. The three peaks near 450 nm, 606 nm, and 720 nm, which are shown in the absorption spectra, are accredited to 4 A2g → 4 T1g, 4 A2g → 4 T2g, 4 A2g → 2 E transitions, respectively. Resonance signals at g ≈ 4.82 and g ≈ 1.99 were observed in EPR spectra which are assigned. FTIR and Raman analysis were carried out to examine the impact of metal fluorides on the structure of bismuth borate glasses.